ASSESSMENT OF RISK FACTORS AND EARLY DIAGNOSIS OF ENDOMETRIAL HYPERPLASIA IN PERIMENOPAUSAL WOMEN - Guli I. Boltaeva; Malokhat F. Yakhshieva; Manzura K. Uzoqova (The Conference Hub, 2025)
Endometrial hyperplasia is an important problem of reproductive health of women in perimenopause, as hormonal changes characteristic of this period increase the risk of its development. The main risk factors are hormonal imbalance, obesity, diabetes, hypertension and hereditary predisposition. The most important diagnostic methods are ultrasound, hysteroscopy with biopsy and molecular genetic testing, which allows for timely detection of pathologies and prevention of their progression. Early detection and timely correction of hormonal levels, as well as prevention of obesity and control of chronic diseases are key measures for the prevention of endometrial hyperplasia and its complications, such as endometrial cancer.
Keywords: Endometrial hyperplasia, perimenopause, early detection, risk factors